Data Report: Molecular and Isotopic Compositions of the Extracted Gas from China’s First Offshore Natural Gas Hydrate Production Test in South China Sea - Jianliang Ye; Xuwen Qin; Haijun Qiu; Wenwei Xie; Hongfeng Lu; Cheng Lu; Jianhou Zhou; Jiyong Liu; Tianbang Yang; Jun Cao; Rina Sa (Energies, 2018)
Three hundred gas samples recovered from SHSC-4 during China’s first gas hydrate production test in the South China Sea were examined for gas component and isotopic composition. According to the gas chromatography analysis, all the gas samples from SHSC-4 are predominated by CH4, with minor N2 + O2, as well as trace amounts of CO2, C2H6, and C3H8. No H2S was detected. The molecular and isotopic data of the gas samples fall into the region of “mixed origin” on the plot of C1/(C2 + C3) − δ13C1, which is close to the microbial origin. The discrimination diagram of δ13C1 − δDCH4 shows that the methane in all of the samples is of microbial origin, and is derived from the CO2 reduction.